'Heat-treatment aqueous two phase system' for purification of serine protease from kesinai (Streblus asper) leaves - Amid, Mehrnoush; Mustafa, Shuhaimi; Abdul Manap, Mohd Yazid (MDPI, 2011)
A ‘Heat treatment aqueous two phase system’ was employed for the first time to purify serine protease from kesinai (Streblus asper) leaves. In this study, introduction of heat treatment procedure in serine protease purification was investigated. In addition, the effects of different molecular weights of polyethylene glycol (PEG 4000, 6000 and 8000) at concentrations of 8, 16 and 21% (w/w) as well as salts (Na-citrate, MgSO4 and K2HPO4) at concentrations of 12, 15, 18% (w/w) on serine protease partition behavior were studied. Optimum conditions for serine protease purification were achieved in the PEG-rich phase with composition of 16% PEG6000-15% MgSO4. Also, thermal treatment of kesinai leaves at 55 °C for 15 min resulted in higher purity and recovery yield compared to the non-heat treatment sample. Furthermore, this study investigated the effects of various concentrations of NaCl addition (2, 4, 6 and 8% w/w) and different pH (4, 7 and 9) on the optimization of the system to obtain high yields of the enzyme. The recovery of serine protease was significantly enhanced in the presence of 4% (w/w) of NaCl at pH 7.0. Based on this system, the purification factor was increased 14.4 fold and achieved a high yield of 96.7%.